Pengaruh Kepemimpinan, Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Choosen Cake And Bakery Di Masaran - Bela Dwi Ramadhani; Asih Handayani (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2024)
Choosen Cake and Bakery in Masaran is one of the bakery shops in Sragen Regency. The aim of this research is to analyze leadership, work environment and work discipline on employee performance. This research is a survey of Choosen Cake and Bakery employees in Masaran. The type of data used is quantitative data. The data source used is primary data. The number of employees at Choosen Cake and Bakery in Masaran in this study was 36 people. This research uses a saturated sampling technique where the entire population can be used as a sample, because the population is relatively small, less than 100 people. Data collection techniques use questionnaires, observation and literature study. Data analysis using multiple linear regression tests, t tests, F tests and coefficient of determination tests were used to analyze the data. The results of the t test show that leadership and work environment have a significant effect on the performance of Choosen Cake and Bakery employees in Masaran, whereas work discipline does not have a significant effect on the performance of Choosen Cake and Bakery employees in Masaran. Keywords: leadership, work environment, work discipline, employee performance